A Comparative Scanning Electron Microscopy Study on Antennal Sensilla of Trissolcus japonicus and Trissolcus plautiae, Egg Parasitoids of Stink Bugs (Pentatomidae). (18th November 2015) - Yang, Shi-Yong; Zhong, Yong-Zhi; Zhang, Jin-Ping; Wang, Xiang-Ping; Zhang, Feng
Abstract : Trissolcus japonicus (Hymenoptera: Scelionidae) and Trissolcus plautiae are solitary endoparasitoids in eggs of stink bugs (Hemiptera: Pentatomidae). These two closely related parasitoids differ in their degree of host specificity. With the aid of scanning electron microscopy, we examined the external morphology, distribution, and abundance of the antennal sensilla of sexes of both species to gain insights into the olfactory mechanism in relation to host selection behavior. Seven types of sensilla were recorded in both species: basiconica, trichodea, grooved-peg, sickle-shaped, chaetica, papillary, and campaniformium sensilla. Sexual dimorphism of antennal structures occurred in both species. Male antennae possessed one more flagellomere and a larger number of olfactory sickle-shaped sensilla than female antennae, indicating that sensilla may be involved in mate or host location. There was a peg gland on the fifth antennomere of male antennae. Compared with males, females had a higher number of trichodea sensilla as well as papillary sensilla, which were not found in males. These sensilla might be involved in host recognition and acceptance during the drumming behavior of both species. No qualitative differences were recorded between the species in antennal structure, or sensilla types or topographical arrangement. However, the abundance of key sensilla was significantly different between species. T. plautiae females and males had larger numbers of trichodea sensilla than those of T. japonicus. T. japonicus females possessed fewer and larger sickle-shaped sensilla compared with T. plautiae females. These differences may provide a morphological basis for understanding the process of host habitat location and recognition in these parasitoids.